DAKWAH DI MEDIA SOSIAL - Amin Supar, Arwani (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2020)
Islamic da'wah has standard aspects and dynamic aspects. The purpose of da'wah and its manhaj are standard, while the means are dynamic and develop according to the demands of the times, one of which is Social Media. This paper discusses the importance of optimizing these (Social Media) facilities for the benefit of da'wah, as well as discussing the Shari'a Signs that preachers must heed in optimizing them.